The Analysis of Ranat-Ek’s Poetic Style in the Piece “Choet.” of Kru Sa-ngob Tongtet - Udomsri, Santi; Kanchanapradit, Jarun (Journal of Music and Performing Arts Khon Kaen University, 2025)
This paper discusses Ranat-Ek’s poetic style in “Choet.” The study aims to demonstrate the characteristics and distinctiveness of Choet’s melody of Ranat-Ek playing, composed by Kru Sa-ngob Tongtet, a master Ranat-Ek player in Chonburi Province, Eastern Thailand. The analysis, based on Phichit Chaiseri’s (2023) selective approach, focusses on examining the distinctive Ranat-Ek poetic idioms of the melody and the concept of creating the melodic phrases. The study’s results reveal that Kru Sa-ngob Tongtet created the Ranat-Ek poetic style using traditional musical principles and philosophy. These principles include considering the principal melody, appropriately interpreting and selecting the melodic phrases, creating unique differences, and creating a melody that rhymes and is enjoyable to listen to. These reflect the knowledge, experience, and musicianship of Kru Sa-ngob Tongtet.